Immunogenicity and safety of quadrivalent versus trivalent inactivated subunit influenza vaccine in children and adolescents: A phase III randomized study. (March 2020) - Vesikari, Timo; Nauta, Jos; Lapini, Giulia; Montomoli, Emanuele; van de Witte, Serge
Highlights: Quadrivalent influenza vaccine (QIV) immunogenicity is comparable to trivalent influenza vaccine (TIV) for shared-lineage influenza strains. QIV immunogenicity is superior to TIV for alternate-lineage influenza B-strains. Inclusion of a second B-strain lineage does not compromise safety. QIVs might decrease the burden of influenza B virus in children and adolescents. Abstract: Objectives: To analyse the immunogenicity and safety of inactivated subunit quadrivalent influenza vaccine (QIV) versus trivalent influenza vaccine (TIV) in children and adolescents 3–17 years of age. Methods: In this phase III, multicentre, double-blind study, 1200 subjects were randomized to receive QIV ( n = 402), TIV with the B-strain of the Victoria lineage ( n = 404), or TIV with the B-strain of the Yamagata lineage ( n = 394). The primary objective was to demonstrate non-inferiority of QIV to TIV for immunogenicity against shared influenza strains, based on post-vaccination hemagglutinin inhibition (HI) titres. Secondary objectives were to show superiority of QIV to TIV for immunogenicity against alternate-lineage B-strains, and to further characterize the immune response by analysing virus neutralization and neuraminidase inhibition titres. Reactogenicity and safety were also compared post-vaccination. Results: QIV elicited a non-inferior response for shared strains (upper limits of the 95% confidence intervals for the HI geometric mean ratios (GMRs) of TIV/QIV < 1.5) and a superior response for alternate-lineage B-strains (HI GMRs of TIV/QIV < 1.0; p < 0.0001) versus TIV. Reporting rates of local and systemic adverse reactions were similar between vaccine arms. Conclusions: QIV had comparable immunogenicity to TIV for shared strains and superior immunogenicity to the alternate-lineage B-strains in TIV. Safety and tolerability profiles were comparable.